SLCO1B1 and CYP3A4 allelic variants associated with pharmacokinetic interactions and adverse reactions induced by simvastatin and atorvastatin used in Peru: Clinical implications - Angel T. Alvarado; Ana María Muñoz; Roberto O. Ybañez-Julca; Mario Pineda-Pérez; Nesquen Tasayco-Yataco; María R. Bendezú; Jorge A. García; Felipe Surco-Laos; Haydee Chávez; Doris Laos-Anchante; Aura Molina-Cabrera; Carmela Ferreyra-Paredes; et al. (GarVal Editorial Ltda., 2023)
Context: Statins reduce the risk of stroke and prevent cardiac events in people with atherosclerosis and diabetes mellitus; and could affect the proliferation, migration, and survival of cancer cells. Aims: To review the most up-to-date and available scientific evidence on the allelic variants of SLCO1B1 and CYP3A4 associated with pharmacokinetic interactions and adverse reactions induced by simvastatin and atorvastatin used in Peru, and their clinical implications. Methods: The bibliographic search was carried out in the PubMed/Medline, Google Scholar and Science Direct databases. The keywords were: "statin", "atorvastatin", "simvastatin" in combination with "pharmacokinetics", "pharmacogenetics", "CYP3A4", "SLCO1B1" or "drug interactions" considering the eligibility criteria defined by the PRISMA-2020 international statement. Results: Scientific evidence indicates a significant association between SLCO1B1 rs4149056 c.521T>C (521CC and 521TC) and increased plasma levels, area under the plasma concentration curve (AUC) and maximum plasma concentration (Cmax) of simvastatin, compared to wild-type SLCO1B1*1/*1 521TT (p<0.05). SLCO1B1 521C is not associated with atorvastatin (p>0.05). Patients with SLCO1B1 521CC had a significantly higher risk of myopathy and rhabdomyolysis induced by simvastatin compared to TT (p<0.05). An association was also found between CYP3A4*1/*22/CYP3A4*3/*22 and increased pharmacokinetic parameters of simvastatin compared to CYP3A4*1/*1 (p< 0.05). Conclusions: Based on the review of the published scientific evidence, it is concluded that individuals carrying the allelic variants SLCO1B1 (c.521T>C), CYP3A4*1/*22 and CYP3A4*3/*22 could be associated with an increase in the pharmacokinetic parameters and with an increased risk of myopathy and rhabdomyolysis induced by simvastatin, and not by atorvastatin.